How can university and national libraries achieve deeper collaboration? - Follett, Brian K. (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2003)
Governments are placing great store in "the knowledge economy" as a key engine for economic and social development in a post-manufacturing world. One result is an acceptance for much increased expenditure on research and advanced teaching and there is much debate, at least in the UK, about how these matters should be organised. Since much of the research (excluding defence) and virtually all the graduate teaching will be undertaken in the universities it follows that one key question in the UK is just what proportion and number of the 100 UK universities should be truly "research-intensive"? The trend, although it can be exaggerated, is towards greater concentration and last year I estimated (Follett, 2002) that the faculty in about 12 of the universities will spend on average 50% of their working year on research and graduate teaching, and 50% on undergraduate teaching. In another 30 universities faculty will spend about 25% of their annual working year on research and 75% on undergraduate teaching. In the remaining 60 universities the time available for research will be much smaller. A second key question relates to the "research infrastructure" needed to support the researchers. It is my contention that access to world-class "research information resources" - at a reasonable cost - is a pre-requisite for any nation's research base. In parallel, of course, the actual means of providing those "research information resources" is changing rapidly and the existing provision through "local" research libraries in individual universities or research institutes, often set alongside other services from the "national" library, is under both financial and technological strain: · Electronic provision of delivering research information "direct to the desk-top" has inverted the means of delivery. This has been developed most strongly in the natural sciences but is likely to develop in all areas of research. · The generation of primary research data on a huge scale - from telescopes, particle physics machines and genomics - is leading to electronic grids and the associated metadata being established so as to process and deliver this material direct to the researcher. Similar opportunities exist for using these technologies in the humanities and the social sciences. · Overall growth in the volume of the world's research continues unabated and is likely to do so for the foreseeable future. · Costs of purchasing research information outstrip inflation (even at constant volume), partly because a true market does not exist.